Foundations for Intrusion Prevention - Alderman, Ian D.; Parter, David W.; Rubin, Shai; Vernon, Mary K. (Gesellschaft für Informatik, 2004)
We propose an infrastructure that helps a system administrator to identify a newly published vulnerability on the site hosts and to evaluate the vulnerability’s threat with respect to the administrator’s security priorities. The infrastructure foundation is the vulnerability semantics, a small set of attributes for vulnerability definition. We demonstrate that with a few attributes it is possible to define the majority of the known vulnerabilities in a way that (i) facilitates their accurate identification, and (ii) enables the administrator to rank the vulnerabilities found according to the organization’s security priorities. A large scale experiment demonstrates that our infrastructure can find significant vulnerabilities even in a site with a high security awareness.
Lecture Notes in Informatics;P-46
Keywords: Intrusion Prevention; 004